Desorption-induced structural changes of metal/Si(111) surfaces: kinetic Monte Carlo simulations - Kocán, Pavel; Sobotík, Pavel; Ošt'ádal, Ivan (Physical review. E, Statistical, nonlinear, and soft matter physics, 2013)
We used a configuration-based kinetic Monte Carlo model to explain important features related to formation of the (√3×√3)R30° mosaic of metal and semiconductor atoms on the Si(111) surface. Using first-order desorption processes, we simulate the surprising zero-order desorption spectra, reported in some cases of metal desorption from the Si(111) surface. We show that the mechanism responsible for the zerolike order of desorption is the enhanced desorption from disordered areas. Formation of the √3×√3 mosaic with properties of a strongly frustrated antiferromagnetic Ising model is simulated by a configuration-sensitive desorption. For substitution of desorbed metal atoms by Si adatoms, fast diffusion of the adatoms on top of a 1×1 layer is proposed as the most probable. Simulations of desorption-induced structural transitions provide us a link between underlying atomistic processes and the observed evolving morphologies with resultant macroscopic desorption fluxes. An effect of the desorption sensitivity on a configuration of neighboring atoms is emphasized.